A mixed-ligand strategy regulates thorium-based MOFs - Huang, Zhi-wei; Hu, Kong-qiu; Mei, Lei; Kong, Xiang-he; Yu, Ji-pan; Liu, Kang; Zeng, Li-wen; Chai, Zhi-Fang; Shi, Wei-Qun (Dalton transactions : an international journal of inorganic chemistry, 2020)
Two novel thorium-based organic frameworks (Th-IHEP-5 and Th-IHEP-6) were assembled from a hexanuclear thorium cluster, porphyrin derivative ligand and linear carboxylic acid ligands via a mixed-ligand strategy. As a stable heterogeneous catalyst, Th-IHEP-5 exhibited high photocatalytic activity for the oxidation of 2-chloroethyl ethyl sulfide (CEES) and the fixation of CO 2 . The good catalytic effect is attributed to the large conjugated system of porphyrin and the photosensitizer enhancing effects of bipyridine. A thorium-based MOF formed via the synergistic construction of porphyrin and bipyridyl based on the mixed-ligand strategy has the effect of enhancing photocatalysis.